On the Rozovskii method to insolate secondary circulation from skewed flow - Morell, Mariana Inés (2016)
Fil: Morell, Mariana Inés. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.